ANALYSIS OF FACTORS AFFECTING STUDENT'S INTEREST TO BECOME TEACHER AT STUDENTS DEPARTMENT OF EDUCATION FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY OF 2016 - Shafira, Jeihan; Sariwulan, Rd. Tuty; Nikensari, Sri Indah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine what factors can effect the interest in becoming a teacher inEconomics Education Students class 2016 at the State University of Jakarta. The factors used inthis study are parental support, self- efficacy, and perception of the teaching profession. Datacollection was carried out in this study using quantitative techniques through questionnaires.The results of this study indicate that there is a positive and significant relationship betweenparental support and interest in becoming a teacher, there is a positive and significantrelationship between self- efficacy and interest in becoming a teacher, and there is a positive andsignificant relationship between perceptions of the teaching profession and interest in becoming ateacher.